THE NATION IN TURMOIL: A POST-COLONIAL CRITIQUE OF SOUTH AFRICAN EDITORIAL CARTOONS - Sizwe Zwelakhe Dlamini, (PEOPLE: International Journal of Social Sciences, 2025)
There seems to be little research that has been done to investigate cartoons from a literary criticism point of view. Cartoons have been given attention mostly in discipline like semiotics as compared to other scholarly perspectives. The aim of this article is to attempt to bridge this gap by observing cartoons through the post-colonial approach as a literary theory. The study adopts systematic visuo-textual analysis as a qualitative research technique since cartoons are the primary sources of data collection and analysis. Through the application of the post-colonial theory, the findings demonstrate that there are depicted socio-cultural, socio-economic, and political issues in Mngadi’s editorial cartoons. These include gender-based violence, identity crisis and immorality, difficult economic living conditions, unemployment, racism, corruption, and leadership concerns in government. This article is significant because it contributes to the scholarship of the cartoon genre in the South African indigenous languages, which has not been given sufficient attention. It provides a different perspective of analysing cartoons by adopting the post-colonial theory as a literary theory. Since cartoons are predominately approached through other approaches like semiotics, this article attempts to demonstrate that this genre can also be examined through literary criticism approaches such the post-colonial theory. This will demonstrate how broad this theory is. While the theory is generally employed to scrutinise prose genres mostly, an attempt is made to show that it can also be valuable in the analysis of editorial cartoons.